2017
DOI: 10.1038/s41598-017-03616-w
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29a Counteracts Synovitis in Knee Osteoarthritis Pathogenesis by Targeting VEGF

Abstract: Synovitis contributes to the development of osteoarthritis (OA) of the knee. MicroRNAs regulate joint microenvironment homeostasis and deterioration. This study was undertaken to characterize the actions of microRNA-29a (miR-29a) to synovial remodeling in OA joints. Synovial specimens isolated from patients with end-stage OA knees showed abundant fibrotic matrix and vessel histopathology concomitant with weak miR-29a expression. In vitro, miR-29a knockdown caused synovial fibroblasts to exhibit high expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 51 publications
(60 reference statements)
1
50
0
Order By: Relevance
“…The miR-29 family is highly expressed in human cartilage during end-stage OA and immediately after destabilization of the medial meniscus (DMM) surgery in mice, highlighting its involvement in early disease and maintaining articular cartilage homeostasis (107). However, miR-29 expression is diminished in end-stage knee OA synovium and associates with synovial lining hypertrophy, inflammation, and fibrosis (108). Intra-articular miR-29a injection maintains synovial homeostasis by targeting VEGF and inhibiting OA-related angiogenesis.…”
Section: Synovial Membrane Contribution To Joint Pathology Via Mirsmentioning
confidence: 99%
“…The miR-29 family is highly expressed in human cartilage during end-stage OA and immediately after destabilization of the medial meniscus (DMM) surgery in mice, highlighting its involvement in early disease and maintaining articular cartilage homeostasis (107). However, miR-29 expression is diminished in end-stage knee OA synovium and associates with synovial lining hypertrophy, inflammation, and fibrosis (108). Intra-articular miR-29a injection maintains synovial homeostasis by targeting VEGF and inhibiting OA-related angiogenesis.…”
Section: Synovial Membrane Contribution To Joint Pathology Via Mirsmentioning
confidence: 99%
“…103,121,137,157,165 However, two of these studies did did show an up-regulation of the miRNA of interest following cartilage extraction and qPCR. 121,157 To date, it is still challenging to carry out in situ hybridization for detection of miRNAs in vivo. However, other studies have demonstrated successful lentiviral uptake by chondrocytes in murine articular cartilage following intra-articular injection.…”
Section: Approaches To Modulate Mirna Function In Vivomentioning
confidence: 94%
“…None of the studies referenced in this review showed over-expression or inhibition of the miRNA of interest in situ in rodent cartilage following intra-articular injection of specific lentiviral constructs. 103,121,137,157,165 However, two of these studies did did show an up-regulation of the miRNA of interest following cartilage extraction and qPCR. 121,157 To date, it is still challenging to carry out in situ hybridization for detection of miRNAs in vivo.…”
Section: Approaches To Modulate Mirna Function In Vivomentioning
confidence: 95%
See 1 more Smart Citation
“…In nasopharyngeal carcinoma, VEGF was proved to be one of the downstream genes of miR-29a by database prediction and dual luciferase reporter gene [12]. After transfection of miR-29a, luminescence reactions of VEGF 3'-UTR luciferase reporter were statistically down-regulated [13]. Therefore, we wonder if similar regulatory effect exists in HCC.…”
Section: Introductionmentioning
confidence: 99%